Pengaruh Perubahan Tarif Pajak dan Metode Penghitungan Pajak dengan Dikeluarkannya PP Pasal 23 Tahun 2018 Terhadap Tingkat Kepatuhan Wajib Pajak UMKM - Inayah, Nur Lailiyatul; Apriliasari, Ria Dini; Juwari, Armadia Eka Nurjannah (Asosiasi Dosen Akuntansi Indonesia, 2024)
This research aims to determine the effect of changes in tax rates and tax calculation methods with the issuance of PP Article 23 of 2018 on the level of compliance of MSME taxpayers. This research adopts quantitative research methods with the Tax Service Office in Central Maluku as the research object. The main population comprises 251 UMKM in the food and beverage sector, officially registered with the Central Maluku Trade Service. The testing methods applied involve normality tests, validity tests, reliability tests, F tests, and T-tests. The research results show that changes in tax rates and tax calculation methods in PP article 23 of 2018 simultaneously affect the level of taxpayer compliance of UMKM employees at service offices—Central Maluku tax. Meanwhile, from partial testing, it was concluded that changes in tax rates and tax calculation methods in PP Article 23 of 2018 had. A partial effect on the level of taxpayer compliance of UMKM employees at the Central Maluku tax service office.